Consuming Argentina in the Name of Love: Cannibalism and Holy Communion in Carne by Eduardo Rovner - Strichartz, Ariel (Latin American Theatre Review, 2008)
While Christian theologians have insisted on the sublime nature of the Eucharist, or symbolic consumption of Christ’s flesh and blood, other scholars have emphasized the contradictory urges of desire and aggression which characterize all metaphors of incorporation –– Communion, cannibalism, sexual intercourse, and eating –– in which the consumer seeks to absorb or subsume the Other. In Carne (1985), the Argentine dramatist Eduardo Rovner collapses all four acts of incorporation, as the work’s female protagonist permits her lover to consume her breast in order to insure his loyalty. However, while Carne underscores the unstable relationship between consumer/consumed and outside/inside, thereby problematizing the relation of power between the male consumer and the consumed feminine body, ultimately the work enacts the misogynist violence of the most recent military dictatorship. (AS, Article in English)